Test Miniaturized and Portable Home-Based Vital Sign Monitor Design with Android Mobile Application - Yusof, Mas Azalya; Xin Fung, Shu; Li Low, Wee; Wen Lim, Chiao; Wen Hau, Yuan (International Journal of Integrated Engineering, 2019)
Frequent or continuous vital sign monitoring could help to decrease mortality rate as early detection of vital sign abnormality allow prompt medical action to be taken for early prevention measurement, especially to elderly people and patients who suffer from chronic disease or infectious disease. However, most of the vital sign monitor are designed for hospital usage and operated by healthcare professionals, which the devices are generally heavy duty, cost-expensive, and complicated user interface for home user. This paper proposes a miniaturized and portable home-based vital sign monitor, named myVitalGear, which can accurately measure heart rate using electrocardiogram (ECG), body temperature and blood oxygen saturation (SpO2), based on Arduino Nano technology. This device aims to enable frequent vital sign monitoring at home by reducing long distance travel to hospital and long waiting hour at hospital. The device consists of an AD8232 chip to acquire ECG for heart rate measurement and further heart rhythm abnormality detection, a high precision DS18B20 temperature sensor for body temperature measurement, and a MAX30100 pulse sensor for SpO2 monitoring. In this device, the Arduino Nano microcontroller acts as the master controller to control all the system peripherals and biomedical sensors to acquire and process all the vital signs.  The device also equipped with simple interface like light emitting diode (LED), liquid crystal display (LCD) and buzzer as the status indicator for layman user.  A mobile application which targeted to Android-based smart phone is also developed to communicate with myVitalGear through Bluetooth wireless communication. The mobile app support the functionalities of displaying the vital sign measurement result, automated short message service (SMS) notification message and user location sending to the healthcare provider or guardian, in case of any vital sign abnormality is detected.  Validation result has shown that the system able to measure vital sign with accuracy of 99.4%, 99.7% and 98.1% for heart rate, body temperature, and SpO2 respectively.